PREVENTIVE MAINTENANCE SISTEM PENDINGIN MESIN YANMAR 6AYM-WST - Farera, Alfathir; Aswin, Fajar; Ramli, Ramli (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Preventive maintenance is a method of maintaining machinery before damage occurs. The Yanmar 6AYM-WST engine serves as the driving force for the dredge pump on the Production Suction Vessel (KIP) at PT. Timah Tbk, which sometimes experiences overheating during operation due to an underperforming cooling system. This final project aims to design a preventive maintenance system for the engine’s cooling system. The methods used include observation, interviews, literature study, and data collection of past breakdowns. The outcome of this study includes an annual maintenance schedule, work specifications, control cards, and machine history cards that are structured and ready for implementation. With this approach, it is expected to reduce the frequency of cooling system failures, improve engine reliability, and achieve operational efficiency of the vessel.